Diseño de un sistema de inyección mediante una bomba horizontal centrífuga HPUMP para aumentar la producción de crudo en un campo petrolero en el departamento del Meta Colombia. (2022)
The present degree work consists of the design of an injection system by means of a horizontal centrifugal pump HPump to increase the production of crude oil in an oil field in the department of meta Colombia, this degree work is divided into 12 chapters whose content is summarized below: The initial chapter gives a brief introduction to water injection in oil fields, including injection patterns and pressure requirements necessary to maintain reservoir pressurization and effective displacement of oil to producing wells. this pressure requirement is given by the discharge of the pump and together with the injection flow rate are the most important variables to take into account during the design of the HPump system.